THE IMPACT OF THE PANDEMIC PERIOD ON THE MOTOR DEVELOPMENT OF 9TH AND 12TH GRADE STUDENTS - Moga Carolina (Sport şi Societate)
This article aims to analyze the impact of the Covid-19 pandemic on the motor 10development of students in the 9th and 12th grades. With home isolation and the transition to online learning, students' physical activity decreased significantly, affecting their physical and psycho-emotional development. Moreover, due to online lessons, the time children spent in front of computers increased considerably, leading to hypodynamia and negatively impacting the physical and mental health of children. In this context, physical education specialists found themselves seeking innovative solutions to organize and conduct the educational process. Our study was based on the best students from the 9th and 12th grades who participated in the national Physical Education Olympiad in 2019 and 2022. The results of over 450 students 18(girls and boys) from all regions of the Republic of Moldova were analyzed. They competed in four practical tests selected from the school curriculum for physical education: athletics, gymnastics, sports games, and general physical preparation. Research methods: bibliographic study; pedagogical observation; ascertaining experiment; testing method; mathematical-statistical method for data processing. The results of our research demonstrated a decrease in the motor preparation level of students after the pandemic period, which was caused by reduced physical activity. This indicates a lower assimilation of practical educational content in the context of online learning. Our research conclusions highlight the necessity of developing a strategy to enhance the process of developing the younger generation by increasing motor activity, improving students' health, and improving the quality of life in the post-pandemic period.